Toxicidade de soluções irrigantes e associações farmacológicas empregadas na pulpectomia de dentes decíduos - Botton, Graziela (2014)
The irrigating solutions used in primary teeth pulpectomies are essential supporters in chemical mechanic preparation, for they come in contact with the dental and periapical tissues, evaluating their biocompatibility is necessary. The aim of this study was to evaluate the in vitro cytotoxicity and genotoxicity of irrigating solutions and pharmacological associations used for sanitizing the root canals of these teeth, by conducting four tests that evaluated the toxicity according to different parameters. Tests of Cell Viability (MTT), Lipid Peroxidation (TBARS), GEMO and Alkaline Comet Assay were performed in the evaluation of major solutions - 1% and 2.5% Sodium Hypochlorite, 2% Chlorhexidine -, auxiliary solutions - 6% Citric Acid and 17% EDTA - and of the associations between major and auxiliary solutions, exposing both human peripheral blood mononuclear cells (MTT, TBARS and Alkaline Comet Assay) in 24h and 72h, and exposing dsDNA, purified calf thymus DNA (GEMO). Data were assessed for normality by Kolmogorov-Smirnov and analyzed by ANOVA followed by post hoc Dunnett's, and Kruskal-Wallis test followed by post hoc Dunn. Values showing p<0.05 were considered statistically significant. Reduction in cell viability was observed in all groups at 24 hours. At 72 hours the reduction has continued, except for EDTA, combinations of (1% and 2.5%) sodium hypochlorite with EDTA (p<0.05) and Chlorhexidine with EDTA (p>0.05). EDTA and 2.5% sodium hypochlorite with EDTA caused lipid peroxidation in 24h, and 1% and 2.5% sodium hypochlorite and three associations with citric acid (p<0.05) had the same effect in 72h. All groups have caused breaks in DNA by Alkaline Comet Assay, 24h and 72h (p<0.05). In the GEMO Test, dsDNA damage was observed in all groups (p<0.05), except for Chlorhexidine with EDTA. Some degree of toxicity was observed in all tested groups. However, Chlorhexidine, among the major solutions, and EDTA, among the auxiliary solutions, were less cytotoxic. Also, the association of these two solutions had less potential toxicity. The results demonstrated the best in vitro biocompatibility in the combination of Chlorhexidine and EDTA.